Gene regulation for inflammation and inflammation resolution differs between umbilical arterial and venous endothelial cells - Michaeli, Julia; Albers, Sebastian; Torre, Carolina de la; Schreiner, Yannick; Faust, Sara; Michaeli, Christoph T.; Michaeli, Daniel; An, Liying; Krämer, Bernhard; Stach-Jablonski, Ksenija; Yard, Benito A. (Scientific reports, 2023)
Systemic inflammation affects the whole vasculature, yet whether arterial and venous endothelial cells differ in their abilities to mediate inflammation and to return to homeostasis after an inflammatory stimulus has not been addressed thoroughly. We assessed gene-expression profiles in isolated endothelial cells from human umbilical arteries (HUAEC) or veins (HUVEC) under basal conditions, after TNF-α stimulation and various time points after TNF-α removal to allow reinstatement of homeostasis. TNF-α regulates the expression of different sets of transcripts that are significantly changed only in HUAEC, only in HUVEC or changed in both. We identified three types of gene regulation, i.e. genes that were significantly regulated after 24 h of TNF-α stimulation but no longer when TNF-α was removed (homeostatic regulation), genes that maintained significantly regulated after TNF-α removal (not homeostatic regulation) and genes that were only significantly regulated when TNF-α was removed (post-regulation). HUAEC and HUVEC quantitatively differed in these types of gene regulation, with relatively more genes being post-regulated in HUAEC. In conclusion our data demonstrate that HUAEC and HUVEC respond intrinsically different to an inflammatory insult. Whether this holds true for all endothelial cells and its relevance for inflammatory insults in different organs during systemic inflammation warrants further studies.
Gesehen am 16.07.2024